THE EFFECT OF COMPENSATION, WORK DISCIPLINE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT THE MAPPI REGENCY REGIONAL SECRETARIAT OFFICE - Maria Kuruway; Arius Andreas Kambu; Ikhwan H. S. (Transpublika Publisher, 2024)
The focus of this study is on the practical issue of employee performance not meeting expectations in the Mappi Regency Secretary's office, with an average achievement rate of 83% over the past three years. Factors such as compensation, work discipline, and job satisfaction have been identified as influences on performance. The main aim of the research is to examine and assess the factors that have a significant impact on performance. The method employed in this study is causality, which seeks to understand the relationships between variables based on established theories. Participants were chosen using accidental sampling, with a total of 60 individuals included in the study. The Likert scale was utilised for measuring variables in this research. Data analysis was conducted using multiple regression statistics through SPSS software. The findings revealed that compensation, work discipline, and job satisfaction collectively had a positive and noteworthy impact on the performance of employees in the Mappi Regional Secretariat. These results support and enhance the conclusions of prior studies and align with existing theories.